Indonesian secondary school EFTL teacher's understanding and practice in developing school based EFL Syllabus - Kamil, Dairabi; Sheikh Ahmad, Ismail (2011)
This study sought to explore Indonesian secondary school EFL teachers’ understanding of the School Based Curriculum Development policy, and examine their practices in developing school-based EFL syllabus. Seven secondary school EFL teachers participated in this study. Data were obtained through semi-structured interviews and were analysed using Thematic Analysis procedure. This study reveals that the participants had different understandings of SBCD. Some of them seemed to have understood the steps of syllabus development partially, while other tended to see the issue as irrelevant. Syllabus development had been mostly practiced as syllabus adaptation or adoption. In the implementation of the curriculum they were facing the problems of lack of understanding and skills in developing the syllabus, workloads and time constraints, unavailability of adequate media, and unreadiness to change old practices in syllabus development.